The Right to Strike and Other Forms of Protest of Persons Performing Gainful Employment Under Civil Law - Tomanek, Artur (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
This article deals with the issue of extending the right to conduct a collective labour dispute to persons performing paid work under civil law contracts, after the entry into force of the Act of 5 July 2018 amending the Act on Trade Unions and Certain Other Acts (Journal of Laws 2018, item 1608). The author considers the question whether and to what extent the right to strike and to take industrial action, provided for in the Act of 23 May 1991 on Resolution of Collective Disputes (consolidated text: Journal of Laws 2020, item 123), extends to civil lawful contractors. The position is presented that the proper application of the above mentioned law to the indicated circle of work contractors cannot mean the deprivation or limitation of their right to strike and to take industrial action. The solutions implemented by the Polish legislator with regard to persons performing work outside the employment relationship are more advantageous and far-reaching in comparison with the requirements resulting from the international labour law acts binding on Poland. However, there are specific problems with applying to these persons some of the regulations included in the Act on Resolution of Collective Disputes. These problems results from the fact that the individual legal relationship between these persons and the entities employing them is based on the provisions of civil law, and not on the Labour Code.